Determinación de dos tipos de dietas a base de amaranto (Amaranthus caudatus) y papa china (Colocasia esculenta) en pollos broiler en la fase de crecimiento-engorde - Carrera Castillo, Jenny Germania (2024)
The present research is aimed at taking advantage of the nutritional characteristics of Amaranth (Amaranthus caudatus) and Chinese Potato (Colocasia esculenta) grains through the use of these ingredients in the growth-fattening phase of broiler chickens. The general objective is to determine two types of diets based on amaranth and Chinese potatoes in broiler chickens in the growth-fattening phase. The procedure that was used for the investigation of two factors, factor A: chickens (growth-fattening) and factor B: Diets (B0: Balanced 100% Control, B1: Balanced 90% + Amaranth 10%, B2: Balanced 90 % + Chinese potato 10%, B3: Balanced 90% + Amaranth 6% + Chinese potato 4%, B4: Balanced 90% + Amaranth 5%+ Chinese potato 5%, B5: Balanced 90% + Chinese potato 6% + Amaranth 4 %, B6: Balanced 90% + Amaranth 8% + Chinese potato 2%). The analysis of results allowed us to statistically determine the best treatment that corresponds to Balanced 90% + Amaranth 6% + Chinese Potato 4%; It was determined as the optimal dose for the growth and development of broiler chickens, registering a final average weight of 3285.60 g/bird, and an increase of 3239.7 g/bird after 45 days of establishing the research. The most efficient feed conversion was obtained in T1 (Balanced 90% + Amaranth 10%) with a value of 1.37 at the end of the research. A mortality percentage of 1.60% was established in the research, so we found that the average goes from 0.00% to 2.90% in treatments T0, T1, T2, T4 respectively, followed by T4 with 0.32% and T3 and T5. with 0.00%. In the economic analysis of the B/C relationship, the growth, development and fattening of broiler chickens between treatments with the addition of diets based on amaranth and Chinese potatoes in the balanced, it was obtained that the best result was T4 (Balanced 90% + Amaranth 5%+ Chinese potato 5%) with 0.24 $ benefit for every dollar invested, in relation to the other treatments.